Effectiveness of a Non-pharmacological Intervention to Control Diabetes Mellitus in a Primary Care Setting in Kerala: A Cluster-Randomized Controlled Trial - Rahul, Arya; Chintha, Sujatha; Anish, Thekkumkara Surendran; Prajitha, Kannamkottapilly Chandrasekharan; Indu, Pillaveetil Sathyadas (Frontiers in Public Health, 2021)
Background Despite being the first Indian state with a dedicated Non-Communicable Disease(NCD) program, glycemic control among a large proportion of patients is low in Kerala. This study tries to find evidence for a standardized non-pharmacological strategy delivered through Junior Public Health Nurses(JPHNs) in achieving and maintaining glycemic control among diabetic patients registered with NCD clinics of primary health care settings. Design A cluster randomized controlled trial was conducted among adult patients with Diabetes Mellitus attending NCD clinics of primary care settings of South Kerala, India. JPHNs of the intervention group received additional module-based training while standard management continued in the control group. Sequence generation was done by random permuted blocks method and a cluster of twelve patients was selected from each of the eleven settings by computer-generated random numbers. Patients were followed up for six months with monthly monitoring of Fasting Blood Sugar(FBS), Post-Prandial Blood Sugar(PPBS), blood pressure, Body Mass Index(BMI), and health-related behaviours. Knowledge and skills/practice of JPHNs were also evaluated. Analysis of Covariance was done to study the final outcome adjusting for the baseline values and a model for glycemic control was predicted using multilevel modeling. Results We analyzed 72 participants in the intervention group and 60 participants in the control group according to the intention-to-treat principle. The intervention was associated with a significant reduction in FBS(p<0.001) and PPBS(p<0.001) adjusting for the baseline values. The achievement of glycemic control was 1.5(95% CI:1.05-2.3) times better with intervention and they showed a better trend of maintenance of glycemic control(FBS,p=0.003 and PPBS,p=0.039). Adjusting for clustering and the baseline values, the intervention showed a significant effect on FBS(B=-3.1, SE=0.57; p<0.001) and PPBS(B=-0.81, SE=0.3; p<0.001) with time. Drug adherence score(p<0.001), hours of physical activity(p<0.001), BMI(p=0.002), fruit intake(p=0.004), and green leafy vegetable intake(p=0.01) were the major predictors of FBS control. The practice/skills score of the JPHNs significantly improved with intervention(p<0.001) adjusting for baseline values. Conclusion A well-designed health worker intervention package incorporated into the existing health system can translate into attitude change and skill development in the health workers which can reflect in the improvement of glycemic control among the patients. Trial registration number-CTRI/2017/11/010622